f(x)=x²-3x zero da função
Soluções para a tarefa
Respondido por
5
f(x) = x² - 3x
0 = x² - 3x
x² - 3x = 0
x.(x - 3) = 0
x = 0
x - 3 = 0
x = 3
R.: x = 0 e x = 3
0 = x² - 3x
x² - 3x = 0
x.(x - 3) = 0
x = 0
x - 3 = 0
x = 3
R.: x = 0 e x = 3
Respondido por
0
Resposta:
f(x) = x² - 3x
0 = x² - 3x
x² - 3x = 0
x.(x - 3) = 0
x = 0
x - 3 = 0
x = 3
R.: x = 0 e x = 3
Explicação passo a passo:
Perguntas interessantes
Química,
1 ano atrás
ENEM,
1 ano atrás
Filosofia,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás